Female athletes' self-representation on social media: A feminist analysis of neoliberal marketing strategies in "economies of visibility". (February 2018) - Toffoletti, Kim; Thorpe, Holly
Existing research into the depiction of female athletes has indicated that while they remain under-represented across traditional and online media outlets, social media is a potential tool for female athletes to redress this lack of coverage, and even contest and rework normative gender and sexual identities in sport. This paper challenges such arguments by offering a feminist thematic analysis of how five international female athletes are using social media to present their sporting and feminine selves within a neoliberal post-feminist moment characterised by individual empowerment and entrepreneurial subjecthood. Adopting a feminist critique of neoliberalism, and critically engaging Banet-Weiser's gendered "economies of visibility", our findings demonstrate that, in a social media environment, female athletes are adopting new strategies for identity construction that capitalise on tropes of agentic post-feminist subjecthood to market themselves, including self-love, self-disclosure and self-empowerment. This paper advances the emerging field of inquiry into athlete social media usage by focusing on the ideological workings of neoliberalised gender discourse not only in the crafting of contemporary sporting femininities in digital spaces, but in recasting feminism as an individualised endeavour firmly located in the market.